Meet the players: local translation at the synapse - Fernandez-Moya, Sandra M.; Bauer, Karl E.; Kiebler, Michael A. (Frontiers in Molecular Neuroscience, 2014)
It is widely believed that activity-dependent synaptic plasticity is the basis for learning and memory. Both processes are dependent on new protein synthesis at the synapse. Here, we describe a mechanism how dendritic mRNAs are transported and subsequently translated at activated synapses. Furthermore, we present the players involved in the regulation of local dendritic translation upon neuronal stimulation and their molecular interplay that maintain local proteome homeostasis. Any dysregulation causes several types of neurological disorders including muscular atrophies, cancers, neuropathies, neurodegenerative and cognitive disorders.